The contribution of women to the economy and social protection especially in relation to unpaid work performed by women in the Caribbean (ECLAC [Port of Spain]TT, 2007)
Examines concepts of unpaid work as performed by women, the care economy and time use. Provides linkages between reproductive and productive work, the importance of such work for economic and social development and women's participation in decision-making.
Keywords: DOMESTIC WORK